2015
DOI: 10.1089/ham.2015.0026
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Excessive Erythrocytosis as a Screening Method for Chronic Mountain Sickness at High Altitude

Abstract: . Noninvasive assessment of excessive erythrocytosis as a screening method for chronic mountain sickness at high altitude. High Alt Med Biol 16:162-168, 2015.-Globally, over 140 million people are at risk of developing chronic mountain sickness, a common maladaptation to life at high altitude ( > 2500 meters above sea level). The diagnosis is contingent upon the identification of excessive erythrocytosis (EE). Current best practices to identify EE require a venous blood draw, which is cumbersome for large-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…TrueHb has been evaluated in adult population in India in a single study with encouraging results [4]. Massimo have poor accuracy in most of the studies, although the precision was greater at higher levels of Hb, similar to our study [6,13,[15][16][17]22].…”
Section: Discussionsupporting
confidence: 80%
“…TrueHb has been evaluated in adult population in India in a single study with encouraging results [4]. Massimo have poor accuracy in most of the studies, although the precision was greater at higher levels of Hb, similar to our study [6,13,[15][16][17]22].…”
Section: Discussionsupporting
confidence: 80%
“…5B). Eight studies 40,42,112,117,[129][130][131]133 found higher mean Hb concentrations (0.3-14.0 g/L) and two 132,139 found lower mean concentrations (9.2−11.0 g/L) by the Pronto-7 compared with the reference. Eight studies 40,42,112,117,[129][130][131][132] were within the ±7% threshold for mean concentration variation for comparisons of the Masimo Pronto-7 with the reference, while two studies exceeded the ±7% bias 133,139 ( Fig.…”
Section: Figure 4 Differences In Mean Hb Of the Other Invasive Pointmentioning
confidence: 94%
“…Ten studies analyzed venous blood by the Masimo Pronto-7 compared with the reference among children aged 6 months to 17 years and adult males and females aged 18 years and older 40,42,112,117,[129][130][131][132][133]139 (Fig. 5B).…”
Section: Figure 4 Differences In Mean Hb Of the Other Invasive Pointmentioning
confidence: 99%
“…However, comparison of earlier results to current POC device performance is limited given ongoing software and hardware revisions [ 30 ]. More recent generations of POC devices (including the device used in this study), have been evaluated in subjects in a variety of clinical settings [ 9 , 31 , 32 ] and in healthy volunteers [ 33 , 34 ], with good correlation between POC hemoglobin and laboratory reference measures. A recent large meta-analysis evaluating the accuracy and precision of current POC devices against central laboratory hemoglobin measurements reported a pooled random-effects mean difference of POC minus central laboratory hemoglobin values of 0.10 ± 1.37 g/dL (limits of agreement − 2.59 to 2.80 g/dL) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%